Elevated zinc transporter ZnT3 in the dentate gyrus of mast cell‐deficient mice. (23rd September 2019) - Wiqas, Amen; LeSauter, Joseph; Taub, Alana; Austin, Rachel Narehood; Silver, Rae
Abstract: Zinc is important in neurogenesis, but excessive levels can cause apoptosis and other pathologies leading to cognitive impairments. Mast cells are present in many brain regions including the hippocampus, an area rich in vesicular zinc. Mast cells contain zinc‐rich granules and a well‐developed mechanism for uptake of zinc ions; both features point to the potential for a role in zinc homeostasis. Prior work using the Timm stain supported this hypothesis, as increased labile zinc was detected in the hippocampus of mast cell‐deficient mice compared to wild‐type mice while no differences in total zinc were found between the two genotypes in the whole brain or other tissues. The current report further examines differences in zinc homeostasis between wild‐type and mast cell‐deficient mice by exploring the zinc transporter ZnT3, which transports labile zinc into synaptic vesicles. The first study used immunocytochemistry to localize ZnT3 within the mossy fibre layer of the hippocampus to determine whether there was differential expression of ZnT3 in wild‐type versus mast cell‐deficient mice. The second study used inductively coupled plasma mass spectrometry (ICP‐MS) to determine total zinc content in the whole dentate gyrus of the two genotypes. The immunocytochemical results indicate that there are higher levels of ZnT3 localized to the mossy fibre layer of the dentate gyrus of mast cell‐deficient mice than in wild‐type mice. The ICP‐MS data reveal no differences in total zinc in dentate gyrus as a whole. The results are consistent with the hypothesis that mast cells participate in zinc homeostasis at the level of synaptic vesicles. Abstract : Mast cell‐deficient mice have more vesicular zinc in the mossy fibre layer of the dentate gyrus than their littermate wild‐type counterparts. Here, we show that they also have elevated levels of ZnT3, the zinc transporter that delivers zinc ions to vesicles. Together, these results are consistent with mast cells having a role in the homeostasis of zinc in the brain.